Peroxiredoxin 2: An Important Element of the Antioxidant Defense of the Erythrocyte - Sadowska-Bartosz, Izabela; Bartosz, Grzegorz (Antioxidants, 2023)
Peroxiredoxin 2 (Prdx2) is the third most abundant erythrocyte protein. It was known previously as calpromotin since its binding to the membrane stimulates the calcium-dependent potassium channel. Prdx2 is present mostly in cytosol in the form of non-covalent dimers but may associate into doughnut-like decamers and other oligomers. Prdx2 reacts rapidly with hydrogen peroxide (k > 107 M−1 s−1). It is the main erythrocyte antioxidant that removes hydrogen peroxide formed endogenously by hemoglobin autoxidation. Prdx2 also reduces other peroxides including lipid, urate, amino acid, and protein hydroperoxides and peroxynitrite. Oxidized Prdx2 can be reduced at the expense of thioredoxin but also of other thiols, especially glutathione. Further reactions of Prdx2 with oxidants lead to hyperoxidation (formation of sulfinyl or sulfonyl derivatives of the peroxidative cysteine). The sulfinyl derivative can be reduced by sulfiredoxin. Circadian oscillations in the level of hyperoxidation of erythrocyte Prdx2 were reported. The protein can be subject to post-translational modifications; some of them, such as phosphorylation, nitration, and acetylation, increase its activity. Prdx2 can also act as a chaperone for hemoglobin and erythrocyte membrane proteins, especially during the maturation of erythrocyte precursors. The extent of Prdx2 oxidation is increased in various diseases and can be an index of oxidative stress.